Piezoelectric materials for Transducers of Ultrasonic Sensitive Elements Based on Bulk Acoustic Waves - Durukan, Yasemin; Peregudov, Aleksandr N.; Popkova, Ekaterina S.; Rybina, Marina A.; Shevelko, Michail M. (IEEE NW Russia Young Researchers in Electrical and Electronic Engineering Conference, 2020)
Criteria for plate piezoelectric transducers of ultrasonic sensitive elements on bulk acoustic waves are determined. The anisotropy of the piezoelectric properties of single crystals of quartz (SiO 2 ), lithium niobate (LiNbO 3 ) and lithium tantalate (LiTaO 3 ) are analyzed. A method for determining the cut of a plate piezoelectric transducer, which provides efficient excitation of various types of waves, based on the angular dependences of the wave velocities propagating in the presence of the piezoelectric effect and in its absence is proposed. The most effective cuts that excite pure transverse waves are determined. The influence of the error in the orientation of the piezoelectric plate on the type of excited waves is estimated.